Secure IT systems : 19th Nordic Conference, NordSec 2014, Tromsø, Norway, October 15-17, 2014, Proceedings - Fischer-Hubner, Simone; Bernsmed, Karin (Lecture Notes in Computer Science, 2014)
This book constitutes the proceedings of the 19th Nordic Conference on Secure IT Systems, held in Tromsø, Norway, in October 2014. The 15 full papers presented in this volume were carefully reviewed and selected from 42 submissions. They are organized in topical sections named: information management and data privacy; cloud, big data and virtualization security; network security and logging; attacks and defenses; and security in healthcare and biometrics. The volume also contains one full-paper invited talk.